Perilaku Remaja Dalam Pemanfaatan Program Pelayanan Kesehatan Peduli Remaja (PKPR) Di Puskesmas Jumpandang Baru - Santi Santi; Cheristina Cheristina (Universitas Pahlawan, 2020)
The Youth Care Health Care Program (PKPR) is a health service to adolescents through special treatment tailored to the desires, tastes and needs of adolescents.This research aims to find out the behavior of adolescents in the utilization of PKPR program on predisposition factor,supporting factors and driving factors. This study uses qualitative design with phenomenological approach. Data collection with focus group discussion (FGD) and indepth interview. FGD is performed on thirteen students who are a target school of Public center. In-depth interviews were conducted on seven ordinary informants, namely community youth who utilize services in health centers, four key informants namely counselors, peer escorts, field officers and PKPR program holders. The results of this study show that the behavior of adolescents in the utilization of PKPR program is not maximal, there are several factors that affect visits to the public center low and less maximal utilization of PKPR. The potential factors related to knowledge have not been thorough, the teenager is not fully aware of the service pkpr in public center so have not utilized the service. Supporting factors related to health care facilities are adequate but need to be effective especially in schools, the driving factors related to the support of health workers have not fully embraced adolescents as a whole. This research can be concluded that health officials further enhance socialization to all adolescents in order to know the importance of utilizing the program and providing support by embracing the youth as a whole, so that the PKPR program in new Jumpandang Public Center can run optimally.